Integrated management of water resources and its impact on the economic and social development of the La Libertad region - Carranza Elguera, Víctor Humberto (2016)
A comprehensive understanding of social management in the La Libertad region requires the analysis and evaluation of substantive achievements and critical factors experienced in the economic, political, cultural and environmental dimensions. Therefore, an analysis of the region's water resources must link them to their role as the most important catalyst of the productive vocation and the forms of political and cultural organization of its regional societies from pre-Hispanic times to the present. In this sense, we are interested, on the one hand, in contrasting, from a cost-benefit approach, both the agro-industrial dynamics and the mining activity and industrial processes installed in the region. On the other hand, we are interested in analyzing the trends of the conflict between the regional comparative advantage expressed in its diversity of water sources (which allow it to expand its agricultural frontier with different types of crops and increase its agroindustrial capacity), with the inadequate use of water resources by mining and industrial companies and by the various population settlements that pollute water sources and rivers. To this must be added flooding or water stress in some areas of the region as a result of climate change. In summary, this paper summarizes the current situation in which the ongoing expectations for boosting economic growth and social development in the La Libertad region are linked to the availability of its water resources. Therefore, our interest is to present not only a description of the spatial distribution of water resources and population, but also the uses of water and its critical factors in relation to economic, political, cultural and environmental conditions. Especially in the current context in which the region is affected by landslides and floods as a consequence of El Niño and in which one of the most important irrigation works in the country is being carried out, such as the Chavimochic Special Project.